Crossroads between transformation and stability. Hospitalisation in Finnish cardiac care as an example - Juha Soivio (AM. Rivista della Società Italiana di Antropologia Medica, 2002)
Crossroads between transformation and stability.Hospitalisation in Finnish cardiac care as an example